Incorporating environmental factors in gait assessments of persons following amputation - Andersom Ricardo Fréz; Christiane Riedi Daniel; Ivo Ilvan Kerppers; João Afonso Ruaro; Jussara Paula da Luz; Marinez Boeing Ruaro (Fisioterapia em Movimento)
Abstract Introduction: Environmental factors have also been recognized to be a component of a multidimensional gait assessment of people living with disabilities, like persons following an amputation. Objective: To investigated whether the environmental factors outlined by the International Classification of Functioning, Disability, and Health (ICF) are considered when evaluating gait following lower limb amputations. Materials and methods: A literature search of the PubMed, EMBASE, CINAHL, and SPORTDiscus databases was performed. The keywords "amputation" and "gait" were combined with the keywords "barriers", "facilitators", and "environmental factors". Searches were performed without language restrictions. All articles containing data about environmental influences on gait functionality after lower limb amputations published during or after 2002, were included. Manuscripts that did not study adults and literature reviews were excluded. Two researchers identified potentially eligible articles and the methods used to assess gait. To make comparisons between scales, the 2 researchers selected the categories from the ICF chapter on environmental factors. Results: Fourteen studies were obtained from the search. Seven studies were duplicates and 4 were excluded. The remaining 3 articles were evaluated. We identified a total of 74 possibilities for categorization according to the ICF environmental factors, but only 7 ICF categories (9.45%) were considered in the studies analyzed. Conclusions: The influence of environmental factors is frequently not considered in the evaluation of gait following a lower limb amputation. Thorough evaluation of gait after lower limb amputation should reflect the complex nature of gait changes, including environmental factors.